Обеспечение точности аппроксимации R/T-характеристики NTC-термистора на основе нейросетевого моделирования - Федин, С.С.; Зубрецкая, И.С. (Технология и конструирование в электронной аппаратуре, 2015)
Разработаны нейросетевые модели для аппроксимации нелинейной R/T-характеристики полупроводникового терморезистивного преобразователя температуры в рабочем диапазоне. На примере термистора типа NTC серии B57703M показано, что использование разработанных нейросетевых моделей позволяет обеспечить более высокую точность аппроксимации по сравнению с полиномиальной моделью Стейнхарта—Харта. Розроблено нейромережні моделі для апроксимації нелінійної R/T-характеристики напівпровідникового терморезистивного перетворювача температури в робочому діапазоні. На прикладі термістора типу NTC серії B57703M показано, що використання розроблених нейромережних моделей дозволяє забезпечити більш високу точність апроксимації в порівнянні з поліноміальною моделлю Стейнхарта—Харта The objective of the study is to develop feed forward neural network models with Back Propagation and Resilient Propagation learning algorithms in order to ensure the accuracy of approximation of R/T-characteristics of NTC-thermistors in the working temperature range. It is shown that the use of the developed neural network models can provide higher accuracy of the approximation in comparison with the known Steinhart-Hart polynomial model. Statistical estimation has shown that for the purpose of solving the problem of neural network approximation of R/T-characteristics of NTC-thermistors, the Back Propagation algorithm is preferable to the Resilient Propagation algorithm. The practical use of the developed models improves the accuracy of individual calibration of NTC-thermistor’s temperature range 218,15 ... 428,15 K.